2017
DOI: 10.1111/pcmr.12596
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulation of melanogenesis by adiponectin via the AMPK/CRTC pathway

Abstract: Several studies observed that adiponectin, an important adipokine that improves glucose metabolism by regulating AMP-activated protein kinase (AMPK) signaling, is dermatologically beneficial. In our recent microarray data, we found that adiponectin expression was lower in lesional skin than in non-lesional skin of melasma patients. Given that AMPK is a key adiponectin signaling mediator, we investigated the role of adiponectin and AICAR, a cell-permeable AMPK activator, in melanogenesis. We herein showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…In particular, full-length adiponectin was reported to suppress melanogenesis. 17 However, in this study, we demonstrated that, unlike fulllength adiponectin, which has an antimelanogenic effect, globular adiponectin, a truncated form of full-length adiponectin, possessed melanogenic activity and that its effects were mediated by activating AMPK-mediated signalling. In addition, it was recently reported that the skin of patients with diabetes had a lower melanin content.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In particular, full-length adiponectin was reported to suppress melanogenesis. 17 However, in this study, we demonstrated that, unlike fulllength adiponectin, which has an antimelanogenic effect, globular adiponectin, a truncated form of full-length adiponectin, possessed melanogenic activity and that its effects were mediated by activating AMPK-mediated signalling. In addition, it was recently reported that the skin of patients with diabetes had a lower melanin content.…”
Section: Discussionmentioning
confidence: 55%
“…In recent studies, effects of adiponectin on skin cells (keratinocytes, fibroblasts and melanocytes) have been reported. In particular, full‐length adiponectin was reported to suppress melanogenesis . However, in this study, we demonstrated that, unlike full‐length adiponectin, which has an antimelanogenic effect, globular adiponectin, a truncated form of full‐length adiponectin, possessed melanogenic activity and that its effects were mediated by activating AMPK‐mediated signalling.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In keeping with their considerable sequence homology, CRTCs have been found to exert overlapping effects on CREB target gene expression; yet knockout studies also reveal distinct phenotypes for each family member [25][26][27][28] . In melanocytes, CRTCs have been proposed as targets for treatment of hyperpigmentary disorders by virtue of their ability to mediate effects of CREB on MITF expression [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%